Prevalence of under-nutrition, associated factors and perceived nutritional status among elderly in a rural area of Puducherry, South India. (July 2016) - Kalaiselvi, S.; Arjumand, Yousuf; Jayalakshmy, R.; Gomathi, Ramaswamy; Pruthu, Thekkur; Palanivel, C.
Highlights: Arm span is taken for calculating Body Mass Index instead of height to account for skeletal changes during ageing process. Over all under nutrition prevalence among elderly is 24.8% including 9.2% of severe under nutrition (BMI < 16 kg/m 2 ). Among the elderly who were perceived their nutritional status as poor 28.9% of them were actually under nourished. Being an elderly male, age >70 years and per capita income <1000 INR were independently associated with under nutrition. Elderly who reported co-morbidities were less commonly associated with under nutrition. Abstract: Background: Under-nutrition among elderly goes undetected, despite their nature of vulnerability to it. Majority of the available literature assessed under nutrition in the facility based settings. We aimed to determine the prevalence of under-nutrition and its associated factors among elderly, in a rural setting. Methods: A community based cross sectional survey was conducted among elderly in one of the randomly selected sub centre catchment area in rural Puducherry, south India. Information on socio demographic characteristics, morbidities and perception on their nutritional status were obtained. Anthropometric measures such as weight and arm span were measured by trained medical graduate as per the standard guidelines. Bodymass index (BMI) less than 18.5 kg/m 2 was considered as under-nutrition. Results: Of total 296 elderly in the study setting, 271 (92%) participated in the study. The prevalence of under nutrition among the elderly was 24.8% (95% CI: 19.7–30.3). More than half of the elderly (58.7%) perceived their nutritional status as poor; of them 28.9% were actually under-nourished. Mean (SD) BMI scores were higher for elderly women compared to that of men [elderly women vs men: 22 (4.6) kg/m 2 vs 21 (3.8) kg/m 2, p = 0.03]. In multivariate analysis, being an elderly male, age more than 70 years and per capita income less than 1000 INR were found to be significantly associated with under-nutrition. Conclusion: In this rural area, one fourth of elderly were under nourished. Urgent inter-sectoral measures including food security programs are required to address this huge nutritional problem in this vulnerable group.